Efficient dye-sensitized solar cells with [copper(6, 6′-dimethyl-2, 2′-bipyridine)2]2+/1+ redox shuttle. Issue 8 (16th January 2017) - Li, Jiajia; Yang, Xichuan; Yu, Ze; Gurzadyan, Gagik G.; Cheng, Ming; Zhang, Fuguo; Cong, Jiayan; Wang, Weihan; Wang, Haoxin; Li, Xiaoxin; Kloo, Lars; Wang, Mei; et al.
Abstract : A copper(6, 6′-dimethyl-2, 2′-bipyridine)2 ] 2+/1+ redox couple was developed as a redox mediator in dye-sensitized solar cells. Abstract : The [copper(6, 6′-dimethyl-2, 2′-bipyridine)2 ] 2+/1+ ([Cu(dmbp)2 ] 2+/1+ ) redox couple, which possesses a distorted tetragonal geometry of a Cu(i ) complex crystal and a distorted tetrahedral coordination geometry of Cu(ii ) complex crystal, has been developed as a redox mediator in dye-sensitized solar cells (DSSCs). The energy of loss for dye regeneration was reduced with a very low but sufficient driving force of only 0.11 eV. A distinct increase in open-circuit voltage ( V OC ) was achieved and a remarkable power conversion efficiency of 10.3% was afforded at 100 mW cm −2 under AM 1.5G condition.